IN BETWEEN ISLAMIC BOARDING SCHOOL: A STUDY OF AL-MUBAROK AL-ISLAM WITHIN THE SOCIAL CHANGES OF SEBERANG KOTA JAMBI - Kusnadi, Edi; Sobur, Kadir; Aziz, Arfan (ADDIN, 2017)
This research was conducted to search the meaning of traditional Islamic boarding schools in Seberang Kota Jambi as an existence legacy of religious traditional institutions in Jambi Malay modern world. The boarding school were slow adapt the modern developments and considered as an educational institution “conservative” who only teach “sky” science by forgetting his footing on the earth. The author tries to conduct a research to determine how the response of a salafiyah Islamic boarding school named al-Mubarok al-Islam toward social change, and how its success. Through a field research and descriptive qualitative method, data were collected through observation, interviews and documentation. The results of research include: First, al-Mubarok al-Islam salafiyah Islamic boarding schools has been growing and has a formal structure that can accommodate all aspects of the pesantren. Second, al-Mubarok al-Islam salafiyah Islamic boarding schools began to provide an opportunity for its students to be able to follow modern world by facilitating them in the national exam and have a certificate in general that can be used in the workplace in general. Third, al-Mubarok al-Islam salafiyah Islamic boarding schools provides the opportunity for students to be able to learn information communication technology nowadays.